2021
DOI: 10.1002/suco.202100250
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Prediction of the elastic modulus of recycled aggregate concrete applying hybrid artificial intelligence and machine learning algorithms

Abstract: Recycled aggregates (RAGs) usage in concrete is surging, inspired by environmental and economic concerns. Regarding predicting various models designed the values of modulus of elasticity (MOE) of concrete with natural aggregates and, in conclusion, they would probably be unreliable when used to concrete with RAG. In the present study, two new gray wolf multi‐layer perceptron neural networks (GWMLP) and gray wolf support vector regression (GWSVR) algorithms were proposed to predict RAG concrete's elastic modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed that in addition to the concentration of chloride ions, increasing the temperature also significantly reduces the chloride ions penetration resistance. [30][31][32] The use of artificial intelligence in the field of civil engineering [33][34][35][36][37][38][39][40][41][42][43][44] today more than ever is being considered. 45 The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of the models, five evaluation criteria are introduced, namely, the correlation coefficient ( R ), root mean squared error (RMSE), mean absolute error (MAE), mean absolute percentage error (MAPE), and relative root mean square percentage error (RRMSE). These statistical parameters are defined as follows 49–53 Rgoodbreak=n()ytrueypredictytrueypredictnytrue2()ytrue2nypredict2()ypredict2 RMSEgoodbreak=1ni=1nytrueypredict2 MAEgoodbreak=1ni=1n||ytruegoodbreak−ypredict MAPEgoodbreak=1ni=1n||ytrueypredictytrue RRMSEgoodbreak=1nfalse∑i=1n()ytruegoodbreak−ypredict21ni=1nytrue ...…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…ML algorithms enable the analysis of multiple variables and the processing of large amounts of data [ 19 ]. ML techniques have proved to be successful in predicting the mechanical properties of concrete, e.g., compressive strength [ 20 , 21 ], tensile strength [ 22 , 23 ], and elastic modulus [ 24 ] Furthermore, ML is efficiently applied in analyzing durability and deterioration processes, e.g., sulfate attack [ 25 ], chloride diffusion [ 26 ], and alkali–silica reaction [ 27 ]. Recently, applications in more sophisticated areas were proposed, e.g., predicting hydration kinetics [ 28 ].…”
Section: Introductionmentioning
confidence: 99%